Studi Komparatif Terhadap Sistem Jual Beli Sawit di Loading Ramp dengan Toke Sawit dalam Perspektif Ekonomi Islam - Fajar Pratama Abdillah; Idwal; Makmur (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to compare the palm oil trading system between loading ramp and toke sawit (middlemen) from the perspective of Islamic economics. A descriptive qualitative approach was used through interviews and documentation conducted in Setia Budi Village, Mukomuko Regency. The findings show that the loading ramp system tends to be more just and transparent than the toke sawit system, although both have their own strengths and weaknesses. The toke system is prone to unfair practices such as weight manipulation and non-transparent pricing, which contradict Islamic muamalah principles. Meanwhile, the loading ramp system aligns more closely with Islamic values due to its standardized procedures and institutional oversight, though it is not entirely free from exploitative practices. The study highlights the importance of justice, transparency, and farmer involvement in creating a Sharia-compliant trading system.